Upaya Peningkatan Hasil Belajar Matematika pada Siswa Kelas 4 Melalui Model Pembelajaran Project Based Learning dengan Berbantu Google Meet - Wahyuti, Wahyuti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this study is to improve mathematics learning outcomes in grade 4 students through the application of the Project Based Learning learning model. The type of research is classroom action research (CAR). The CAR model used was the C. Kemmis & Mc Taggart spiral model which was carried out in 2 cycles. Data collection techniques are test techniques and non-test techniques. The research instrument using questions and observation sheets. The data analysis technique used is comparative descriptive. Based on the results of the study, it was shown that the cognitive domain of mathematics learning outcomes based on the percentage of completeness of pre-cycle, first and second cycle learning outcomes was 45,1%; 73,0%; 86.8%.